Setting up a patient complaint system in the national primary healthcare network in Lebanon (2016–2020): Lessons for Low‐ and Middle‐Income Countries. (8th October 2021) - Hammoud, Rawan; Laham, Sandy; Kdouh, Ola; Hamadeh, Randa
Abstract: Over the past decade there has been a renewed global commitment towards building people‐centred healthcare systems and enhancing the capture of patient complaints. Literature from Low‐ and Middle‐Income Countries (LMICs) on patient complaints is sparse. In 2016, the Primary Healthcare (PHC) Department at the Ministry of Public Health in Lebanon, developed a full grievance (complaint or inquiry) redress system. This paper aims to describe the development of the national grievance handling system and analyse 5 years' worth of grievance data (2016–2020). The study entailed a retrospective analysis of grievances relating to the care of patients treated in 237 Primary Health Centres in the national PHC network in Lebanon, lodged through the central grievance uptakes channels between 1 January 2016 and 31 December 2020. Between 1 January 2016 and 31 December 2020, the PHC Department at the ministry of health received 562 grievances from a total of 389 unique beneficiaries Management issues made up an overwhelming 70% of all grievances, followed by relationships (20%) and clinical issues (6%). Findings indicate the need to enhance the healthcare administration, monitoring and workflow at the PHC centres and to promote the utilisation of grievance systems. The study outlines lessons learned for building grievance systems in LMICs.